2019
DOI: 10.1111/fcp.12480
|View full text |Cite
|
Sign up to set email alerts
|

Is TNF inhibitor exposure a risk factor for amyotrophic lateral sclerosis?

Abstract: TNFα modulation has been reported to be either beneficial or detrimental in amyotrophic lateral sclerosis (ALS) and therefore appears as a key issue. We analysed the relationship between TNFα inhibitor (TNFi) exposure and ALS. We performed descriptive analysis of ALS reports in patients treated with TNFi, registered in the French Pharmacovigilance Database (FPvD) and disproportionality analyses by the ‘case’/’non‐case’ method in FPvD and worldwide database (Vigibase®). The 8 retrieved ALS cases from the FPvD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…1a–c ). To our knowledge, this represents one of the longest prolongations of lifespan reported in this model and is especially notable given that individually targeting TNFα in SOD1 mice 20 or human patients 21 or targeting Il-1 family members 22 , 23 , C1q 24 , or the inflammatory astrocyte marker gene C3 (Supplementary Fig. 2 ) in various SOD1 mouse models has little or no effect.…”
Section: Resultsmentioning
confidence: 84%
“…1a–c ). To our knowledge, this represents one of the longest prolongations of lifespan reported in this model and is especially notable given that individually targeting TNFα in SOD1 mice 20 or human patients 21 or targeting Il-1 family members 22 , 23 , C1q 24 , or the inflammatory astrocyte marker gene C3 (Supplementary Fig. 2 ) in various SOD1 mouse models has little or no effect.…”
Section: Resultsmentioning
confidence: 84%
“…In SOD1 mutant mice, signaling through the TNF receptor 2 lead to motor neurone death (126), whereas signaling through TNF receptor 1 was harmful (127). The recent suggestions that TNF inhibitors could be a risk factor for ALS (128) could indicate that TNF is beneficial in some way.…”
Section: Tumor Necrosis Factor (Tnf)mentioning
confidence: 99%
“…Here we provide the key points of the article by Petitpain et al as follows: The sample consisted of 160 ALS cases from 43 to 75 years old under TNFi inflammatory rheumatism treatment, retrieved from the French Pharmacovigilance Database and the VigiBase ® . From the disproportionality analyses, it seems that there are significant associations between TNFi exposure and ALS, regardless of the comparators. The findings concluded that an alleged association between TNFi and ALS should be interpreted cautiously, nevertheless TNFi could act as a predisposing or risk factor. However, it seems that TNFi should be avoided in patients with a known risk of ALS and stopped in case of ALS neurological signs. …”
mentioning
confidence: 99%
“…The novelty of the study reported by Petitpain et al lies in the real‐life registrations of the ALS cases under TNFi therapy. Petitpain et al showed a significant association between TNFi exposure and ALS by a systematic analysis of two pharmacovigilance databases (French and worldwide).…”
mentioning
confidence: 99%